2D/4D proportion and preoperative anxiety: Is there an association? (Annals of Medical Research, 2021)
Aim: The proportion of an individual’s index finger to their ring finger, their 2D/4D proportion, is influenced by prenatal sex hormones and is known to be higher in women. It has been related to certain psychological, behavioral and physiological characteristics. Therefore, we aimed to discover whether 2D/4D proportion is related to preoperative anxiety.Materials and Methods: We included 108 ASA I or II patients with an age range of 18 to 65 years who were to undergo elective surgery. The APAIS-A and APAIS-B tests were used to determine the patients’ anxiety levels and their desire to obtain information regarding the preoperation. Digit lengths were quantified via a digital caliper with 0.01 mm sensitivity. 2D/4D proportions were measured bilaterally, allowing us to determine the differences between the fingers of both hands. Patients were grouped according to their 2D/4D proportions as ≥1 mm and
Keywords: 2D/4D proportion; APAIS scale; preoperative anxiety